Evaluation of the toxicity of aqueous extracts of Aframomum melegueta, Picralima nitida, and Garcinia cola in Wistar rats - Kabongo TJB; Luvingisa LA; Ngoie MP; Musuyu MD; Musunga MA; Kabamba MW; Pyana PP (Open Journal of Biological Sciences - Peertechz Publications, 2023)
In order to determine the risks to human health associated with the use of certain medicinal plants, including Aframomum melegueta, Garcinia kola and Picralima nitida in a preclinical evaluation of the resistance, a pool of these three aqueous extracts was given once daily for ten days by gavage in Wistar rats. Haematological and biochemical analyzes after oral administration revealed a decrease in certain hepatic biomarkers such as glucose, Alanine Aminotransferase (ALT), etc., and renal biomarkers such as urea, creatinine, and creatinine kinase); increase in certain biomarkers such as Aspartate Transaminase (AST), an indicator of kidney and liver capacity.